EDUKASI PENINGKATAN PENCEGAHAN PERILAKU PERUNDUNGAN DAN KEKERASAN SISWA SEKOLAH DASAR MELALUI PENDEKATAN BEHAVIORISTIK - Devi Wening Astari; Sekarningrum, Anggun Anindya; Lokita , Raden Arditya Mutwara (Jurnal Abdi Insani, 2024)
The recent increase in cases of bullying and violence committed by elementary school students is very concerning. Cases of bullying and violence against students also occurred at SDN Kejambon 2, Ngemplak. To overcome this problem, education was carried out to prevent bullying and violence through a behavioristic approach. The aim is to provide education and assistance to students in grades 4, 5 and 6 so that they better understand bullying and violence, recognize types of bullying, provide an understanding of the impacts of bullying, and provide an understanding of things that can be done to avoid bullying behavior. The method used is through a campaign in the form of training related to the ins and outs of bullying and violence by starting with a pre-test to determine students' knowledge, then continuing with training while inviting students to do a sharing session, ending with a post-test so that after the training students can have awareness and mindset that bullying behavior should not be done. The results of the paired sample correlation test showed a correlation coefficient value of 0.609 with a significance value (Sig.) of <0.001. While the Paired Samples Test showed a Sig. (2-tailed) value of <0.001, with an average pre-test value of 60.00 and a post-test result value of 82.39. These results mean that there is an influence of education in increasing the prevention of bullying and violent behavior in students of Kejambon 2 Elementary School. The recommendation for Kejambon 2 Elementary School is to immediately form a task force, have counselors and build synergy with student guardians in order to optimize the handling of bullying in the Kejambon 2 Elementary School environment.